Epidemiology and clinical course of bronchiolitis in hospitalized children in tertiary care hospital in Kashmir - Malik, Mohammad Imran; Wani, Khurshid Ahmad; Baba, Ruhail Ahmad; Kumar, Irshad Ahmad (International Journal of Contemporary Pediatrics, 2023)
Background: Bronchiolitis is the commonest lower respiratory tract infection in children < 2 years of age and is responsible for the majority of their pediatrician visits and hospital admission during the winter season. The aim of this study was to describe the epidemiological data, seasonal trends, clinical characteristics, and outcomes of children admitted with bronchiolitis in pediatric hospital GMC Srinagar. Methods: This was a retrospective observational study in children less than 2 years of age admitted in department of pediatrics in GMC Srinagar. Data were collected through review of the medical records of patients with a diagnosis of bronchiolitis on discharge and analyzed through SPSS 20. Results: A total of 228 infants were enrolled in the study. The majority were males (60.08%). The median age on admission was 5.5 months, exclusive breastfeeding was the mode of feeding in majority and 8.77% were ex-preterm. Respiratory syncytial virus (RSV) was identified in majority (103) and admission peak was from October to March. Most of the patients presented on day 3 of the illness. Most patients 45.17% were having feeding difficulties and chest auscultation was normal in about 22% of the children. Oxygen supplementation was administered to 85.52% of the children. The 32 children (14.03%) required admission to PICU. Mechanical ventilation was required in 6 children (18.75%). No death occurred in infants while in the hospital. Conclusions: RSV has been found to be the main responsible virus. Management of bronchiolitis is usually symptomatic as recommended by most of the guidelines.